TRANSFORMING DIGITAL LIBRARIES THROUGH AI: ANALYSING PERSONALIZATION STRATEGIES FOR IMPROVED USER SATISFACTION - Gulati, Nidhi; Sharma, Sapna; Tyagi, Sudhir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores how digital libraries can leverage AI-driven personalization to enhance user engagement, satisfaction, and overall experience. The research investigates the effectiveness of AI-driven marketing strategies in promoting digital library resources across diverse cultural and economic contexts, emphasizing the importance of localized adaptations. Using a quantitative research design, data was collected from 570 respondents in Hyderabad, India, through a structured survey. Key constructs measured include AI-driven personalization in digital libraries, user loyalty, satisfaction, cultural and economic contexts, marketing effectiveness, and localization. Multiple and moderated regression analyses revealed that AI-driven personalization significantly enhances user loyalty and satisfaction in the context of digital libraries. The effectiveness of AI-driven marketing strategies varied across cultural and economic contexts, with localization significantly boosting effectiveness. Interaction terms indicated that culturally sensitive and economically relevant strategies are more effective when localized to meet user preferences. The findings highlight the importance of personalized, culturally aligned, and locally adapted marketing strategies in digital libraries to enhance user engagement and achieve superior outcomes. These insights provide practical and theoretical contributions, emphasizing the need for digital libraries to invest in AI technologies and tailor their outreach strategies to local contexts for sustainable growth in user engagement.